2012
DOI: 10.1021/nl302318f
|View full text |Cite
|
Sign up to set email alerts
|

Hopping Conduction in Mn Ion-Implanted GaAs Nanowires

Abstract: We report on temperature-dependent charge transport in heavily doped Mn(+)-implanted GaAs nanowires. The results clearly demonstrate that the transport is governed by temperature-dependent hopping processes, with a crossover between nearest neighbor hopping and Mott variable range hopping at about 180 K. From detailed analysis, we have extracted characteristic hopping energies and corresponding hopping lengths. At low temperatures, a strongly nonlinear conductivity is observed which reflects a modified hopping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
(41 reference statements)
1
35
0
Order By: Relevance
“…In such conditions lighter (Ga,Al)As appear darker. STEM images taken along the [11][12][13][14][15][16][17][18][19][20] zone axis permit to determine clearly the interfaces between different shells along the NW length. The tomography was performed with the following parameters: electron probe size 0. paramagnetic test sample) are achieved by degaussing the magnetometer with an oscillating magnetic field of decreasing amplitude.…”
Section: Tem Imaging and Elemental Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…In such conditions lighter (Ga,Al)As appear darker. STEM images taken along the [11][12][13][14][15][16][17][18][19][20] zone axis permit to determine clearly the interfaces between different shells along the NW length. The tomography was performed with the following parameters: electron probe size 0. paramagnetic test sample) are achieved by degaussing the magnetometer with an oscillating magnetic field of decreasing amplitude.…”
Section: Tem Imaging and Elemental Mappingmentioning
confidence: 99%
“…7 These options are all well encompassed within a bottom-up approach: a controlled growth of ferromagnetic nanowires of (preferably) semiconductor origin, may serve as an ideal route to provide the necessary architecture and resulting functionalities. This is predominantly the reason of the strong ongoing interest in the elaboration of nonequilibrium growth of (Ga,Mn)As dilute ferromagnetic semiconductor (DFS) nanowires (NWs) [8][9][10][11][12][13][14][15][16][17][18][19][20][21] which would exhibit or even surpass the excellent micromagnetic properties of the prototype, epitaxial (Ga,Mn)As layers. 22 This challenge has proven to be a formidable one.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper, the author ascribed the increase in conductivity to a substitutional activation of Ga in the Ge nanowires; the conductivity decrease at high doses is attributed to defect generation and, finally, amorphization. Paschoal et al [33] reported that the transport characteristic of Mn + -implanted GaAs nanowires is governed by nearest neighbor hopping at high temperature ( T > 180 K) and Mott variable range hopping at low temperature (50 K < T < 180 K). Yan et al [34] reported that conductivity of the carbon nanotube (CNT) networks is enhanced by H ion beam irradiation.…”
Section: Reviewmentioning
confidence: 99%
“…As in some of the crystalline counterparts [7,23,24] the magnetic properties of these diluted amorphous alloys could be explained by the magnetic polaron model at low temperatures, but their coercive field at T < T C seems to be higher with respect to what was found in the crystalline counterpart; also the limit concentration below which it is possible to obtain the dilute system free of metallic precipitates is increased with respect to the crystalline material. [23] The variable range hopping conduction mechanism and the strong carrier localization of this amorphous alloy does not substantially differ from what is observed in the crystalline diluted system (GaMnAs or GeMn), [25,26] pointing out the strong role of the disorder induced by the random position of the manganese atoms in the host semiconductor matrix that is present in the crystalline DMSs as well.…”
Section: Discussionmentioning
confidence: 70%